CALCULATION OF FINANCIAL LOSSES IN VILLAGE CREDIT INSTITUTIONS: THE AUTHORITY OF THE REGIONAL INSPECTORATE FROM AN ADMINISTRATIVE LAW PERSPECTIVE - Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes; I Wayan Widiastina (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
One of the important principles of good governance is transparent and accountable state financial management. Deviations in financial management can cause state financial losses that can disrupt state stability and reduce public trust. The authority to calculate and determine state financial losses is constitutionally vested in the Supreme Audit Agency (BPK). However, in the practice of regional governance, the Government Internal Supervisory Apparatus, in this case the Regional Inspectorate, is also involved in the audit process related to indications of state financial losses. The problem becomes more complex when this authority is applied to Village Credit Institutions (Lembaga Perkreditan Desa), which are customary financial institutions in Bali Province. This study aims to analyze the concept of state financial losses from an administrative law perspective and examine the authority of the Regional Inspectorate in calculating losses at Village Credit Institutions. The method used in this study is a normative legal research method with a statutory regulatory approach and a conceptual approach. The legal materials used include statutory regulations, legal literature, and relevant scientific articles. The research results indicate that the Regional Inspectorate has the authority to conduct audits and calculate indications of losses as part of the government's internal oversight function, but the authority to determine final state financial losses remains with the Supreme Audit Agency (BPK). Therefore, clarity in the regulation of authority is needed to avoid overlapping authority between supervisory institutions.